Pelatihan Diversifikasi Pangan Pakcoy Berbasis Pertanian Hidroponik dan Desain Pada Kemasan Produk - Dyah Ayu Sri Hartanti; Siti Nur Qomariyah; Umi Kulsum Nur Qomariah; Akmalia Putri Bilqisthi; Hanum Wahda Zuhriyah; Novi Ria Ananta; Rizki Anisa; Zakiyyah Marhamah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas KH. A. Wahab Hasbullah, 2025)
This study aims to empower the community of Plosokerep Village by enhancing skills in food product diversification and digital packaging design. The main problems faced by the partners are the lack of innovation in processing hydroponic pakcoy vegetables and limited abilities in promotional design. This community service program employed the Participatory Action Research (PAR) method with a Service Learning (SL) approach, emphasizing the active involvement of the community as partners. The activities included training in the development of innovative products such as pakcoy noodles and pakcoy nuggets, as well as training in business logo design using the Canva application. The results indicated an improvement in participants’ skills in both food processing and digital graphic design, which contributed to increasing the selling value and competitiveness of the products. Furthermore, the program had positive impacts on the economic independence of greenhouse groups and health cadres, strengthened social solidarity, and supported community nutrition education. It is recommended that this program be further developed through advanced training in digital marketing, product quality evaluation, and diversification of pakcoy-based food products to encourage the sustainability of community-based enterprises.